Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s42003-019-0453-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac interstitial tetraploid cells can escape replicative senescence in rodents but not large mammals

Abstract: Cardiomyocyte ploidy has been described but remains obscure in cardiac interstitial cells. Ploidy of c-kit+ cardiac interstitial cells was assessed using confocal, karyotypic, and flow cytometric technique. Notable differences were found between rodent (rat, mouse) c-kit+ cardiac interstitial cells possessing mononuclear tetraploid (4n) content, compared to large mammals (human, swine) with mononuclear diploid (2n) content. In-situ analysis, confirmed with fresh isolates, revealed diploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 98 publications
3
15
0
Order By: Relevance
“…Developing embryos are comprised exclusively of diploid cells, whereas tetraploid cells are depleted from the epiblast lineage by mid‐gestation stage, excluded from the ICM, and instead reside among trophoblast layer contributing to extra‐embryonic membranes . The extra‐embryonic membrane localization of blastocyst‐injected cCICs (Figure ) is consistent with tetraploid DNA content of in vitro‐expanded cCIC . Tetraploid (4n) content of cCICs used for this study was confirmed by nuclear DNA content and larger nuclear size compared with sperm (haploid, 1n) or bone marrow cells (BMC, diploid, 2n) by flow cytometry and microscopy‐based nuclear intensity quantification (Figure A‐C).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Developing embryos are comprised exclusively of diploid cells, whereas tetraploid cells are depleted from the epiblast lineage by mid‐gestation stage, excluded from the ICM, and instead reside among trophoblast layer contributing to extra‐embryonic membranes . The extra‐embryonic membrane localization of blastocyst‐injected cCICs (Figure ) is consistent with tetraploid DNA content of in vitro‐expanded cCIC . Tetraploid (4n) content of cCICs used for this study was confirmed by nuclear DNA content and larger nuclear size compared with sperm (haploid, 1n) or bone marrow cells (BMC, diploid, 2n) by flow cytometry and microscopy‐based nuclear intensity quantification (Figure A‐C).…”
Section: Resultssupporting
confidence: 70%
“…Taken further, our group found that relatively short‐term 2D cell culture for five serial passages results in loss of cell‐specific identity markers and increased homogeneity in a CIC subpopulation enriched for tyrosine‐protein kinase kit or CD117 (c‐Kit + ) cardiac interstitial cell (cCIC) compared with correspondingly selected freshly isolated cells by single‐cell RNA‐Seq transcriptional profiling . Findings such as these support the contention that CIC isolation and propagation conditions exert profound influences upon biological and functional properties, consistent with our recent reports of hypoxic culture conditions antagonizing mitochondrial dysfunction and senescence in human cCICs as well as tetraploid conversion of murine cCICs . Surprisingly, despite irrefutable evidence of alterations following in vitro expansion of primary CIC isolates, there are essentially no studies to document the extent of such changes as permanent or transient and whether CICs undergo another round of phenotypic and functional adaptation following reintroduction to their native environment of in vivo myocardium.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Both studies combined bulk transcriptomic data on laser capture microdissected samples, with single-cell Taqman ® sc-qPCR through Fluidigm Dynamic Arrays, to show the beneficial factors secreted by the cells of interest, post-injection in the infarcted hearts. More recently, three studies have focused on the controversial population of c-kit + progenitor cells [ 83 , 84 , 85 ]. In all cases, scRNAseq analysis showed that freshly isolated c-kit + cells are heterogeneous and include cells with mesenchymal or endothelial features; thus, they are unlikely to differentiate in CMs.…”
Section: Cardiac Scrnaseq To Elucidate In Vitro Differentiation Anmentioning
confidence: 99%